Homo Legens: A person Reading - Stepanova, M.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
The article raises the problem of the psychology of fiction as a form of art from the standpoint of cultural and historical methodology. Separately, based on the ideas of M.M. Bakhtin about the dialogic nature of the text and A.N. Leontiev about the communicative nature of art, issues related to the creation of works of art and their understanding are considered, which is reflected in the sections "the work of the author" and "the work of the reader". The meeting of the author and the reader means the birth of Homo Legens - the Reading Man: this publication is devoted to the study of this phenomenon. Fiction (as the author's work) can be analyzed in two ways: on the one hand, it acts as an object of psychological research, and on the other - its subject, an independent carrier of psychological knowledge. In the first case, literature is either an object of scientific and psychological study, or its means; in the second, the possibility of treating literature as a carrier of extra-scientific psychological knowledge is substantiated, which determines its its psychotechnical effect on the reader. The reader's perception of a literary work (the reader's work) is analyzed from artistic and scientific positions, which complement each other. Based on L.S. Vygotsky's ideas about the activity of aesthetic experience and P.Ya. Galperin's doctrine of interiorization, the point of view is substantiated according to which the reader's understanding of a literary work is a process of its active recreation, which is consonant with V.F. Asmus's ideas about reading as creativity. In conclusion, using fiction as an example, a conclusion is made about the productivity of turning to scientific and non-scientific (literary) sources of psychological knowledge in developing issues of the psychology of art. В статье с позиций культурно-исторической методологии поднимается проблема психологии художественной литературы как вида искусства. Отдельно, отталкиваясь от представлений М.М. Бахтина о диалогичности текста и А.Н. Леонтьева о коммуникативной природе искусства, рассматриваются вопросы, связанные с созданием художественных произведений и их пониманием, что получило отражение в разделах «Работа автора» и «Работа читателя». Встреча автора и читателя означает рождение Homo Legens - Человека читающего. Исследованию этого феномена и посвящена данная публикация. Художественную литературу (как работу автора) можно анализировать двояко: с одной стороны, она выступает предметом психологического исследования, а с другой - ее субъектом, самостоятельным носителем психологического знания. В первом случае литература представляет собой либо объект научно-психологического изучения, либо его средство; во втором - обосновывается возможность отношения к литературе как к носителю вненаучного психологического знания, чем и обусловлено ее психотехническое воздействие на читателя. Восприятие литературного произведения читателем (работа читателя) анализируется с художественных и научных позиций, которые взаимодополняют друг друга. С опорой на представления Л.С. Выготского об активности эстетического переживания и учение об интериоризации П.Я. Гальперина обосновывается точка зрения, согласно которой понимание литературного произведения читателем есть процесс его активного воссоздания, что созвучно представлениям В.Ф. Асмуса о чтении как творчестве. В заключение на примере художественной литературы делается вывод о продуктивности обращения к научным и вненаучным (литературным) источникам психологического знания при разработке вопросов психологии искусства.